Proceedings of the Fourteenth Workshop on Innovative Use of NLP for Building Educational Applications 2019
DOI: 10.18653/v1/w19-4441
|View full text |Cite
|
Sign up to set email alerts
|

Content Modeling for Automated Oral Proficiency Scoring System

Abstract: We developed an automated oral proficiency scoring system for non-native English speakers' spontaneous speech. Automated systems that score holistic proficiency are expected to assess a wide range of performance categories, and the content is one of the core performance categories. In order to assess the quality of the content, we trained a Siamese convolutional neural network (Siamese CNN) to model the semantic relationship between key points generated by experts and a test response. The correlation between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Craighead et al (2020) explored text-based auxiliary tasks and train models in a multi-task manner using speech transcription and found the L1 prediction task to benefit the scoring performance. Recent work also explored specific aspects of speech scoring like response content scoring, where, the features from the transcription of response are modeled with a respective question to learn the relevance of response (Yoon and Lee 2019;Qian et al 2018). Qian et al (2019) build over the work done by Qian et al (2018) and model acoustic cues, prompt, and grammar features to improve scoring performance.…”
Section: Related Workmentioning
confidence: 99%
“…Craighead et al (2020) explored text-based auxiliary tasks and train models in a multi-task manner using speech transcription and found the L1 prediction task to benefit the scoring performance. Recent work also explored specific aspects of speech scoring like response content scoring, where, the features from the transcription of response are modeled with a respective question to learn the relevance of response (Yoon and Lee 2019;Qian et al 2018). Qian et al (2019) build over the work done by Qian et al (2018) and model acoustic cues, prompt, and grammar features to improve scoring performance.…”
Section: Related Workmentioning
confidence: 99%
“…The research in automated scoring of non-native English speech has shown that it is possible to automatically evaluate the content relevance of a response (Yoon and Lee, 2019). It was demonstrated that fine-tuning Transformer-based models is especially beneficial for this task (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these groups had separate requirements in terms of entry points, inputs, outputs, and documentation. Only by addressing all of these diverse requirements were we able to achieve wider adoption of RSMTool for model evaluation (Rupp et al, 2019;Yoon and Lee, 2019;Kwong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%